Analisa Hukum Akibat Pencabutan Kekuasaan Orang Tua menurut Hukum Perdata - Hadri Jasman Hutasoit; Firdaus Firdaus; Dasrol Dasrol (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The protection of children's rights in the family is closely related to the parents. Parents are thebiological father or mother, and the family is a small community unit consisting of father and/or mother andchildren. Parents, families and communities are responsible for protecting and maintaining in accordancewith what is imposed by law. As parents in civil relations with their children have what is called parentalauthority. In 2020 the number of cases increased, for cases of children victims of economic neglect (livingrights) totaling 239 cases, while for cases of neglect of children victims of neglect of parents and families,there were 107 cases. It is not uncommon for one case to involve more than one victim and perpetrator.Even though parental authority is inherent in civil relations, however, parental authority can be revoked inaccordance with Articles 319a to 319m of the Indonesian Civil Code with Article 49 of the same marriagelaw, in 319a it explains that the revocation of parental power is caused by parents abusing their power.parents or too neglect the obligation to care for and educate one or more children. So the problem ofrevoking parental power over children is very interesting to study in a thesis with the following problemformulation: what are the responsibilities of parents towards children who have been revoked by theirparental rights, what efforts should parents make towards children's rights even though parental authorityhas been unplugged.The type of research used in this legal research is the normative juridical method. This research isdescriptive in nature, namely a study that aims to make a clear and detailed picture of the problem. The datasources used are secondary data and tertiary legal materials. The data collection technique in this studyused the literature review method.Based on the results, it can be concluded that the legal consequences of revocation of parentalcustody are contained in Article 319j, namely parents who are released or dismissed from their powers areobliged to provide allowances to the trusteeship board or temporary guardian for the maintenance andeducation costs of children who have been withdrawn from their powers. . Thus it is clear that the legalconsequences of revocation of parental custody of children, both in Law Number 1 of 1974 concerningMarriage, Law Number 23 of 2002 concerning Child Protection, and the Civil Code have legalconsequences that are the same, that is, parents who have had their powers revoked remain responsible forthe cost of living for their children.Keywords: Parental Power, Revocation of parental authority, Civil Law.